THE ANALYSIS OF FACTORS DETERMINING THE DIFFERENCES OF PERINATAL LOSSES DUE TO CONGENITAL MALFORMATIONS IN THE REGIONS OF THE RUSSIAN FEDERATION (ACCORDING TO THE STATE AND DEPARTMENTAL STATISTICS) - E. N. Baibarina; Z. SorKh.okina; E. А. Kogan (Вопросы современной педиатрии, 2012)
The article contains the results of comparative analysis of the structure of medico-biological factors affecting characteristics of perinatal losses due to congenital malformations in the regions of the Russian Federation in 2010. The authors represent the objective comparative analysis of the management of obstetric, gynecological and neonatal medical healthcare quality at different levels and stages.